1997
DOI: 10.1159/000217446
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms of Fibrinogen, Antithrombin III and Plasminogen in Chronic Liver Diseases of Increasing Severity

Abstract: Acquired deficiencies of fibrinogen, antithrombin III and plasminogen are reported in liver disease, and it is known that their plasma levels fluctuate during the day. The aim of this study was to investigate the circadian rhythms of these three factors in chronic liver disease. Five groups of subjects were considered: (A) 15 healthy controls; (B) 15 patients with hepatic alcoholic steatosis; (C) 15 patients with chronic active hepatitis; (D) 15 patients with compensated cirrhosis of the liver, and (E) 15 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…The diurnal variation in fibrinogen in middle-aged adults agrees with previous studies on much smaller samples 22,23,31 and shows a peak in the early afternoon, with values that decrease throughout the rest of the day. Previous studies of D-dimer on a small number of subjects (nϽ15) did not find a diurnal variation in D-dimer, 24,25 although another small study did report a morning peak.…”
Section: Diurnal Variationssupporting
confidence: 89%
See 1 more Smart Citation
“…The diurnal variation in fibrinogen in middle-aged adults agrees with previous studies on much smaller samples 22,23,31 and shows a peak in the early afternoon, with values that decrease throughout the rest of the day. Previous studies of D-dimer on a small number of subjects (nϽ15) did not find a diurnal variation in D-dimer, 24,25 although another small study did report a morning peak.…”
Section: Diurnal Variationssupporting
confidence: 89%
“…8 This is supported by other smaller studies. 7,16 As well as seasonal effects, variable reports exist of a diurnal pattern in fibrinogen 12,22,23 and D-dimer, 24 -26 whereas t-PA shows a morning peak with levels that tend to decline during the day; 12,24,27,28 vWF has been reported to show no diurnal variation in 1 small study. 28 Diurnal variation may be an important source of heterogeneity or bias, and standardization for sampling time may be important in populationbased studies, as well as in using these variables for additional coronary heart disease risk prediction in individuals.…”
Section: Clinical Perspective P 1003mentioning
confidence: 93%
“…17,18 Some research has reported that the circadian rhythm is effective on the fibrinogen and plasminogen. 19,20 In a study by Kanabrocki et al, platelet and fibrinogen aggregation were reported in the afternoon and in the morning, respectively. 21 Yasuda et al stated that the thromboplastin time had a significant reduction in two of the four intervals studied.…”
Section: The Effect Of Acute Training and Circadian Rhythm On Blood Hmentioning
confidence: 99%
“…Pasqualetti et al also reported a circadian rhythm in AT activity, with an acrophase in the early afternoon hours. 108 Because the intraindividual and within-day variability of these parameters is reportedly higher than the corresponding intra-assay variability, these changes might be real and reflect a significant daily fluctuation. At variance with these studies, however, Akiyama et al 101 did not observe any circadian variation in PC and AT levels.…”
Section: Circadian Variation Of Anticoagulant Factorsmentioning
confidence: 99%